The Impact Of Trade Facilitation On Seaweed Exports In Indonesia - Sadhina, Risma; Widayanti, Sri; Syah, Mirza Andrian (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2025)
Indonesia has great potential in seaweed exports, but its utilization was still not optimal due to various barriers in the trade system. This study aimed to analyze the development of Indonesian seaweed exports to seven main destination countries during 2013–2023, assess the condition of the trade facilitation index, and examine the influence of these variables on exports. The method used was a quantitative approach with a gravity model and panel data. The research results showed that the GDP of destination countries and the quality of trade and transport infrastructure had a positive and significant effect on Indonesia's seaweed exports. Conversely, Indonesia's GDP, logistics competence, and customs efficiency did not have a significant effect. The corruption perception index showed a significant negative effect on exports. These findings confirmed that external factors such as the purchasing power of destination countries and the quality of infrastructure had a major influence, while internal factors such as corruption were a major obstacle. Therefore, export enhancement strategies should be focused on trade governance reforms, strengthening export infrastructure, and developing markets in countries with high trade facilitation indices.